A Brief Observational History of the Black-Hole Spacetimes. (18th February 2015) - Kundt, Wolfgang
Abstract : In this year (2015), black holes (BHs) celebrate their 100th birthday, if their birth is taken to be triggered by a handwritten letter from Martin Schwarzschild to Albert Einstein, in connection with his newly found spherically symmetric vacuum solution.